Melastomataceae Juss. de floresta montana no complexo Serra das Lontras - Jardim, Alessandra Quirino Bertoso dos Santos (2010)
This paper presents a study on the family Melastomataceae in the Serra das Lontras Complex focusing on the taxonomic diversity and ecological aspects of the group. Eleven genera and 43 species were recorded: Aciotis D. Don (1), Bertolonia Raddi (3), Clidemia D. Don (3), Graffenrieda DC. (1), Henriettea DC. (1), Huberia DC. (1), Leandra Raddi (12), Miconia Ruiz & Pav. (14), Ossaea DC. (3), Pterolepis Miq. (1) and Tibouchina Aubl. (3). Eight species were recorded for the first time in the state of Bahia and two species previously known only from type material were recollected: Huberia carvalhoi Baumgratz and Ossaea sulbahiensis D’el Rei Souza. Three new species were also found: two Bertolonia and one Leandra. We present identification keys for the genus and species, as well as illustrations, descriptions, comments about morphology and environmental aspects for each species and geographical distribution.